POTENSI POLA PERJALANAN EKOWISATA JAWA TIMUR PASCA PANDEMI COVID-19 - Asmoro, Agung Yoga; Yusrizal, Firdaus (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p02, 2021)
The COVID-19 pandemic has plunged the tourism sector. Tourism industries have ceased operations in line with travel restrictions imposed by most countries. With various considerations, the tourism sector must be reopened. Kemenparekraf said ecotourism has the potential to survive in the post-COVID period. East Java with a variety of ecotourism destinations has the potential to become a leading destination. On the other hand, a pandemic caused changes in tourist behavior. Government policies that prioritize ecotourism; the advantages of East Java's ecotourism attractions; as well as a shift in the tourists' behavior who tend to travel to locations close to home, had an impact on changing tourism patterns in East Java. This research was conducted with a qualitative approach case study to reveal tour patterns in East Java, especially in the cities of Surabaya, Tuban, Batu, Malang City, Malang Regency, and Banyuwangi which contributed to 50% of East Java’s domestic tourist visits. This research was conducted in two phases, where the first stage (literature studies) guides the next phase of qualitative data in the form of interviews with tourism stakeholders. Our findings are that the majority of East Java tourists conduct tours in the regency/city where they live, ecotourism has not become the main choice of domestic tourists, local governments need to further develop potential natural attractions as ecotourism attractions, and existing ecotourism travel patterns are not yet optimized.